Being asked to tell an unpleasant truth about another person activates anterior insula and medial prefrontal cortex - Littlefield, Melissa M.; Dietz, Martin J.; Fitzgerald, Des; Knudsen, Kasper J.; Tonks, James (Frontiers in Human Neuroscience, 2015)
“Truth” has been used as a baseline condition in several functional magnetic resonance imaging (fMRI) studies of deception. However, like deception, telling the truth is an inherently social construct, which requires consideration of another person’s mental state, a phenomenon known as Theory of Mind. Using a novel ecological paradigm, we examined blood oxygenation level dependent (BOLD) responses during social and simple truth telling. Participants (n = 27) were randomly divided into two competing teams. Post-competition, each participant was scanned while evaluating performances from in-group and out-group members. Participants were asked to be honest and were told that their evaluations would be made public. We found increased BOLD responses in the medial prefrontal cortex, bilateral anterior insula and precuneus when participants were asked to tell social truths compared to simple truths about another person. At the behavioral level, participants were slower at responding to social compared to simple questions about another person. These findings suggest that telling the truth is a nuanced cognitive operation that is dependent on the degree of mentalizing. Importantly, we show that the cortical regions engaged by truth telling show a distinct pattern when the task requires social reasoning.